The 5-HT1A agonist 8-OH-DPAT increases consumption of palatable wet mash and liquid diets in the rat. - Dourish, C; Cooper, S; Gilbert, F; Coughlan, J; Iversen, S (1988)
The 5-HT1A agonist 8-OH-DPAT, at a dose of 30 micrograms/kg, enhanced the consumption of sweetened wet mash and sweetened milk in non-deprived rats. In partially satiated rats, sensitivity to the hyperphagic effect of 8-OH-DPAT on wet mash intake was substantially increased, so that the minimally effective dose was reduced to 3 micrograms/kg. Similarly, 8-OH-DPAT was more efficacious in increasing milk intake in satiated rats. Thus, 30 and 40 micrograms/kg 8-OH-DPAT produced a 4-fold increase of milk intake in completely satiated rats compared to a 2-fold increase in partially satiated animals at a dose of 30 micrograms/kg. The increased intake of liquid and wet mash diets observed after treatment with low doses of 8-OH-DPAT argues against the involvement of non-specific gnawing in the increased consumption of solid food produced by the drug. Rather, the data suggest that 8-OH-DPAT may specifically stimulate appetite by counteracting a tonic serotonergic inhibition of feeding. The present experiments also showed that 8-OH-DPAT attenuates fenfluramine-induced anorexia which is thought to depend on increased serotonergic neurotransmission.